Pengaruh Adsorben Karbon Aktif Dan Bleaching Earth (Be) Terhadap Kemurnian Stearin Miniplant Politeknik Kampar - Hanifah Khairiah; Antonius Sihotang (Jurnal Sains dan Ilmu Terapan, 2019)
The use of chemical fertilizers that are not equalized with organic fertilizers can damage the soil fertility and it is not environmentally friendly, because the microorganisms which have a role in decompose process will not develop. On the other hand, the high prices of organic fertilizers make farmers reluctant to use organic fertilizers. To solve this problem, farmers could be used microorganism with culturing process. The purpose of this research is to determine the comparison of EM4 with culturing process and EM4 in commercial liquid organic fertilizer that applied in mustard plants. This study used a completely randomized design with three treatments, where the treatment was explained as P0 (control), P1 (EM4 commercial), P2( EM4 by culturing process ). The data were taken in the form of plant height, leaf width, and number of leaves of mustard plants. The conclusion of this study was the application of EM4 with culturing process can accelerate the growth of new leaves, the length and width compared with commercial EM4 and control plants.